Shrimp culture : - Kungvankij, P. (Aquaculture Department, Southeast Asian Fisheries Development Center, 1986)
This book provides a description of principles and practices of shrimp culture at one point in time and documents both historical events and conditions now. It also tries to look into the future. The volume provides both practical information about shrimp culture, as well as basic information on shrimp biology. It should be of value to researchers, consultant practitioners and potential investors in the marine shrimp culture industry.